From snacking on diversity and inclusion to systemic organizational consumption. Issue 4 (8th July 2021) - Roberts, Robin
Abstract : Purpose: Most global organizations have a diversity and inclusion (D&I) statement and initiatives to advance equity within their organizations though minimal traction is evidenced by what is espoused. This paper aims to demonstrate how to make progress in D&I generalizable to global workplaces. Design/methodology/approach: Approaching D&I initiatives as collectivist working society bridges gaps in resourcing, powering and actualizing D&I organizationally unlike being demonstrated in companies where D&I is facilitated by majority groups. Findings: Qualitative studies show that though people believe they are behaving morally toward others, they mostly have hidden concerns about infringing on discrimination laws. Originality/value: This paper provides human resource practitioners with a systemic method of advancing D&I equitably while promoting organizational citizenship comparable to thriving workplaces.